Low-cost 3D-printed inverted microscope to detect Mycobacterium tuberculosis in a MODS culture. (January 2022) - Salguedo, Mario; Zarate, Guillermo; Coronel, Jorge; Comina, Germán; Gilman, Robert H.; Sheen, Patricia; Oberhelman, Richard; Zimic, Mirko
Abstract: MODS, an assay for diagnosis of tuberculosis and drug-susceptibility, is based in the microscopic observation of the characteristic cords of Mycobacterium tuberculosis colonies grown in liquid media. An inverted optical microscope (100× magnification) is required to observe and interpret MODS cultures. Unfortunately, the cost of commercial inverted microscopes is not affordable in low resource settings. To perform a diagnosis of tuberculosis using the MODS assay, images with modest quality are enough for proper interpretation. Therefore, the use of a high cost commercial inverted optical microscope is not indispensable. In this study, we designed a prototype of an optical inverted microscope created by 3D-printing and based on a smartphone. The system was evaluated with 226 MODS TB positive and 207 MODS TB negative digital images. These images were obtained from 10 sputum samples MODS positive and 10 sputum samples MODS negative. The quality of all images was assessed by a qualified technician, in terms of adequacy to interpret and classify them as positive or negative for tuberculosis. The quality of the images was considered appropriate for MODS interpretation. All the 20 samples were correctly classified (as TB positive/negative) by reading with the prototype 3D-printed inverted microscope.